Dietary cocoa inhibits colitis associated cancer: a crucial involvement of the IL-6/STAT3 pathway - Saadatdoust, Z.; Pandurangan, A.K.; Sadagopan, S.K.A.; Esa, N.M.; Ismail, A.; Mustafa, Mohd Rais (2015)
Patients with inflammatory bowel disease (IBD) are at increased risk for developing ulcerative colitis-associated colorectal cancer (CRC). The interleukin-6 (IL-6)/signal transducer and activator of transcription (STAT)-3 signaling regulates survival and proliferation of intestinal epithelial cells and play an important role in the pathogenesis of IBD and CRC. Cocoa is enriched with polyphenols that known to possess antioxidant, anti-inflammatory and antitumor activities. Here, we explored the antitumor effects and mechanisms of cocoa diet on colitis-associated cancer (CAC) using the azoxymethane/dextran sulfate sodium model, with a particular focus on whether cocoa exerts its anticancer effect through the IL-6/STAT3 pathway. We found that cocoa significantly decreased the tumor incidence and size in CAC-induced mice. In addition to inhibiting proliferation of tumor epithelial cells, cocoa suppressed colonic IL-6 expression and subsequently activation of STAT3. Thus, our findings demonstrated that cocoa diet suppresses CAC tumorigenesis, and its antitumor effect is partly mediated by limiting IL-6/STAT3 activation. In addition, cocoa induces apoptosis by increased the expressions of Bax and caspase 3 and decreased Bcl-xl. Thus, we conclude that cocoa may be a potential agent in the prevention and treatment of CAC. (C) 2015 Elsevier Inc. All rights reserved.